Thailand : 2010 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Thailand. (IMF Staff Country Reports; Country Report, 2010)
The Thai economy has demonstrated its strength in its rapid rebound from the global crisis. But the loss of its former dynamism has slowed trend growth and left it largely dependent on exports. Executive Directors encourage an infrastructure-led growth strategy to make a difference to Thailand's medium-term outlook. The significant obstacles to this strategy is that large infrastructure projects are particularly complex, with difficulties at the design, contracting, and implementation phases. An infrastructure-led growth strategy would also require budgetary resources and strengthening the medium-term fiscal framework.